Adverse reactions to the first and second doses of Pfizer-BioNTech COVID-19 vaccine among healthcare workers. Issue 7 (July 2022) - Maruyama, Ayano; Sawa, Teiji; Teramukai, Satoshi; Katoh, Norito
Abstract: Introduction: In the current coronavirus infection 2019 (COVID-19) pandemic, the messenger RNA vaccines have been shown to help protect high-risk groups from COVID-19. Among healthcare workers vaccinated with Pfizer-BioNTech COVID-19 vaccine, a survey was conducted to analyze the relationship between the incidence and severity of adverse reactions after vaccination. Methods: We conducted a prospective self-reported survey of adverse reactions among healthcare workers vaccinated with the Pfizer-BioNTech COVID-19 vaccine (Comirnaty®) in Japan. After the first and second dose of vaccine, local and systemic reactions for 8 days after vaccination were reported by volunteer participants using a website. After receiving vaccination, 374 respondents participated in this matched-pair study. Results: Both the incidence and severity of adverse reactions tended to be higher after the second vaccine dose than after the first dose. However, the incidence and numeric rating scale (NRS) score of muscle and skin pain were nearly the same after the first and second doses. In a comparison by sex, women had significantly higher incidence and NRS scores for adverse reactions such as headache, skin pain, erythema, and itching. The results also showed that younger age groups had higher incidence rates and NRS scores for all adverse reactions investigated, except for muscle pain, compared with older age groups. Conclusion: Some adverse reactions to the Pfizer-BioNTech Comirnaty® COVID-19 vaccine showed gender and age differences. However, generally speaking, all side reactions disappear within a week. Therefore, these side reactions are not a significant concern in recommending vaccination.